Pengaruh Struktur Kepemilikan Terhadap Manajemen Laba Pada Perbankan di Indonesia - Ibnu Muttaqin (UNSIKA (Universitas Singaperbangsa Karawang), 2019)
Important information for investors that contains information about the company's performance and its accomplishments over a certain period is included in the income statement. One of the qualitative characteristics of financial statements is that they are presented fairly. Public companies and private companies differ in their demands for accounting information and manager's opportunistic behavior. This study aims to obtain new empirical evidence whether there is an influence of ownership structure on earnings management in banks in Indonesia. The population used is all commercial banks in Indonesia in 2012-2014. Sample by using purposive sampling method. The procedure of collecting data by method of documentation. Hypothesis testing using Mann-Whitney U test. The results of the faithful representation side calculated by earnings management, obtained the earnings management of public banks higher than private banks and the difference is both significant. This result concluded that opportunistic behavior is more dominant than demand of high quality of accounting information at public bank in Indonesia.